Springer handbook of robotics - Siciliano, Bruno; Khatib, Oussama (Springer Handbooks, 2016)
The second edition of this handbook provides a state-of-the-art overview on the various aspects in the rapidly developing field of robotics. Reaching for the human frontier, robotics is vigorously engaged in the growing challenges of new emerging domains.